Photocopying from bound volumes : a study of machines, methods, and materials - Hawken, William R. (Chicago : Library Technology Project, American Library Association, 1962)
The main purpose of the project was to test and evaluate equipment, processes, and materials which could be used for making copies of pages from bound volumes. The book also aims at clearing away some of the confusion that has come about from the seemingly endless proliferation of photocopying materials and devices masquerading under a bewildering array of meaningless trade names.
Accompanied by "Supplements no. 1-3."
aia 16/06/2017
Loans
Keywords: Photomechanical processes